IMPLEMENTASI KEGIATAN KARTINIAN SEBAGAI UPAYA PENANAMAN NILAI EMANSIPASI PADA SISWA SD NEGERI 13 PALEMBANG - Kurnia Utami; Delviya Pransiska; Sakinah Dwi Putri; Adam Helsinki Umar; Gilang Satria; Indah Sakinah; M. Faiz Alfaridzi; Lisnaini; Syska Purnamasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of Kartinian activities as an effort to instill the values of emancipation in students at SD Negeri 13 Palembang is understood not merely as a commemoration of Kartini Day, but as a means to introduce the values embodied in R.A. Kartini’s struggle, such as equality, courage, and independence. The research conducted by the author employed a qualitative descriptive method, utilizing data collection techniques such as observation and documentation. The research results indicate that the Kartinian activities, which were carried out through a traditional costume contest and poetry reading as part of a series of events, as well as a coloring contest and a quiz, were able to provide meaningful learning experiences for the students. These activities encouraged students to be more confident, brave enough to perform, work together, and respect one another regardless of gender; thus, the Kartinian activities were quite effective in instilling the values of women’s empowerment in elementary school.